AKTIVITAS FISIK DAN FAKTOR LAIN YANG MEMPENGARUHI SIKLUS MENSTRUASI PADA WANITA USIA SUBUR (WUS) DI WILAYAH DESA MOJOAGUNG KABUPATEN PATI - Sri Wahyuni; Naomi Parmila Hesti Savitri (Journal of Innovative and Creativity (Joecy), 2026)
The menstrual cycle is an important indicator of women's reproductive health and is influenced by hormonal balance in the body. Changes in the menstrual cycle can occur due to various factors, including physical activity. Other factors such as stress level, nutritional status, sleep quality, dietary patterns, and contraceptive use may also affect menstrual regularity. This study aimed to determine the relationship between physical activity and other factors affecting the menstrual cycle among women of reproductive age in Mojoagung Village, Pati Regency. This study used a quantitative method with a cross-sectional design. The sample consisted of 80 women of reproductive age selected using purposive sampling techniques. Data were collected using questionnaires assessing physical activity, diet, stress level, sleep quality, nutritional status, and menstrual cycle patterns. Data were analyzed using univariate and bivariate analysis. The results showed that most respondents had moderate physical activity (55%), normal menstrual cycles (62.5%), and physical activity was associated with menstrual cycle regularity. Other factors related to menstrual cycle changes were stress level, nutritional status, and sleep quality.